Outcome of multimodal MRI-guided intravenous thrombolysis in patients with stroke with unknown time of onset. Issue 1 (11th February 2019) - Zhao, Jie; Zhao, Hongmei; Li, Runtao; Li, Jiangtao; Liu, Chang; Lv, Juan; Li, Yanan; Liu, Wei; Ma, Dongpu; Hao, Huaihai; Xiao, Xinguang; Liu, Junzhong; et al.
Abstract : Objective: Intravenous tissue plasminogen activator (tPA) is the standard therapy for patients with acute ischaemic stroke (AIS) within 4.5 hours of onset. Recent trials have expanded the endovascular treatment window to 24 hours. We investigated the efficacy and safety of using multimodal MRI to guide intravenous tPA treatment for patients with AIS of unknown time of onset (UTO). Methods: Data on patients with AIS with UTO and within 4.5 hours of onset were reviewed. Data elements collected and analysed included: demographics, National Institutes of Health Stroke Scale (NIHSS) score at baseline and 2 hours, 24 hours, 7 days after thrombolysis and before discharge, the modified Rankin Scale (mRS) score at 3 months after discharge, imaging findings and any adverse event. Results: Forty-two patients with UTO and 62 in control group treated within 4.5 hours of onset were treated with intravenous tPA. The NIHSS scores after thrombolysis and/or before discharge in UTO group were significantly improved compared with the baseline (p<0.05). Between the two groups, no significant differences in NIHSS score were observed (p>0.05). Utilising the non-inferiority test, to compare mRS scores (0–2) at 3 months between the two groups, the difference was 5.2% (92% CI, OR 0.196). Patients in the UTO group had mRS scores of 0-2, which were non-inferior to the control group. Their incidence of adverse events was similar. Conclusions: Utilising multimodal MRI to guide intravenous only thrombolysis for patients with AIS with UTO was safe and effective. In those patients with AIS between 6 and 24 hours of time of onset but without large arterial occlusion, intravenous thrombolysis could be considered an option.